Issues and Challenges in Acculturation Among The Rohingya Refugees in Bangladesh: A Systematic Literature Review - Farhana Zamil Tinny; Abdul Latiff Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
Relocating to a new country and adapting to a new environment and culture can be stressful. Refugees undergo an acculturation process to accommodate and adjust to the new culture. With wide-ranging research on the Rohingya refugee situation, there is still a need for study in academia, specifically in the field of intercultural communication, in these communities. Therefore, this study aims to conduct a systematic literature review to identify the issues and challenges the Rohingya refugees experience while integrating with the local community in Bangladesh. The review process followed PRISMA 2020 guidelines, a seven-step checklist as an assessment tool to ensure the quality of the study. This study systematically searches multiple sources of information to extract, review, and synthesize data from the prominent database on the Rohingya refugee's acculturation process. Studies published within the last 5 years were eligible for review. The PRISMA 2020 flow diagram presents data identification, screening, excluding, and including criteria for the review process. Scholarly empirical studies have been reviewed from prominent online databases, such as SAGE Journals, Taylor & Francis, SCOPUS, Emerald Insight, Science Direct, Web of Science, and Wiley. Key issues and challenges identified in adapting to Bangladeshi culture are- access to fundamental requirements, challenges and coping strategies to assimilate, implementation of the revised policy, access to educational resources, healthcare infrastructure, and integration with the host community. There is a need for proper attention from the respective stakeholders to address the issues and challenges during the acculturation process in Bangladesh.